SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN TINGKAT KECERDASAN MAHASISWA DALAM PROSES PEMBELAJARAN MENGGUNAKAN METODE FUZZY ASSOCIATIVE MEMORY: Array - Syahriani, Budi (JiTEKH, 2020)
As we know, the development of science, especially in the field of information technology, which is increasingly developing from year to year, in the field of information technology cannot be separated from the use of computers. Computers are a set of tools or machines that work systematically and function as electronic data processing tools that have the ability to be very fast and precise with very large quality. So STMIK Budidarma Medan, as an academic institution that is oriented towards science and information technology, establishes a curriculum that is flexible and able to accommodate existing developments. The author conducted a research at the Al-Hikmah Tanjung Balai Higher Education Foundation. From the research the writer carried out the stages and finally concluded and got the right title, namely: "Decision Support System to Determine the Level of Student Intelligence in the Learning Process Using the Fuzzy Associative Memory Method". This program is designed to have a foundation, namely to motivate students in carrying out their learning process to be even better and to include increasing the degree of the campus, in processing the data every semester is required to input the value data obtained by students through the Visual Studio program. Net 2008.